Unexpected A·T(WC)↔A·T(rWC)/A·T(rH) and A·T(H)↔A·T(rH)/A·T(rWC) conformational transitions between the classical A·T DNA base pairs: A QM/QTAIM comprehensive study. Issue 18 (11th August 2018) - Brovarets', Ol'ha O.; Tsiupa, Kostiantyn S.; Hovorun, Dmytro M.
Abstract: In this study, using QM/QTAIM calculations in the continuum with ε  = 1 under normal conditions, we have revealed for the first time the nondissociative A·T(WC)↔A·T(rWC)/A·T(rH) and A·T(H)↔A·T(rH)/A·T(rWC) conformational transitions. It was established that they proceed via the essentially nonplanar transition states (С1 symmetry) through the intermediates, which are wobbled conformers (С1 symmetry) theoretically predicted in our previous work (Brovarets' et al., Frontiers in Chemistry, 2018, 6:8, 10.3389/fchem.2018.00008) of the classical А·Т DNA base pairs—Watson–Crick А·Т(WC), reverse Watson–Crick А·Т(rWC), Hoogsteen А·Т(Н) and reverse Hoogsteen А·Т(rН). At this, the A·T(H)↔A·T(rWC) and A·T(WC)↔A·T(rH) conformational transformations are controlled by the transition states (TSs) stabilized by the participation of the intermolecular (T)N3H···N6(A) H‐bond (∼3.70 kcal·mol −1 ) between the imino group N3H of T and pyramidilized amino group N6H2 of A. Gibbs free energies of activation for these processes consist 12.22 and 11.11 kcal·mol −1, accordingly, under normal conditions. TSs, which control the A·T(WC)↔A·T(rWC) and A·T(H)↔A·T(rH) conformational transitions are stabilized by the participation of the intermolecular (T)N3H···N6(A) H‐bond (5.82 kcal·mol −1 ) and bifurcating intermolecular (T)N3H···N6(A) (5.00) and (T)N3H···N7(A) (0.61 kcal·mol −1 ) H‐bonds, accordingly. Notably, in these two TSs amino group N6H2 of A is significantly pyramidilized; Gibbs free energies of activation for these reactions are 19.07 and 19.71 kcal·mol −1, accordingly. Abstract : First‐principles calculations reveal new conformational transformations of the classical А·Т DNA base pairs—Watson–Crick А·Т(WC), reverse Watson–Crick А·Т(rWC), Hoogsteen А·Т(Н), and reverse Hoogsteen А·Т(rН)— via the essentially nonplanar transition states. While the DNA double helix contains the canonical Watson–Crick base pairs, which provides storage and precise transfer of the genetic information, their replacement with the non‐Watson–Crick base pairs leads to perspective interesting practical applications